Realizacja założeń edukacji zdrowotnej w norweskim systemie szkolnictwa = Implementation of the objectives of health education in the Norwegian school system - Kilanowska, Jolanta (Journal of Education, Health and Sport, 2016)
Kilanowska Jolanta. Realizacja założeń edukacji zdrowotnej w norweskim systemie szkolnictwa = Implementation of the objectives of health education in the Norwegian school system. Journal of Education, Health and Sport. 2016;6(10):337-352. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.162891 http://ojs.ukw.edu.pl/index.php/johs/article/view/3951 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 20.10.2016. Realizacja założeń edukacji zdrowotnej w norweskim systemie szkolnictwa Implementation of the objectives of health education in the Norwegian school system Jolanta Kilanowska Åsen skole, Lørenskog Norwegia Słowa kluczowe: edukacja zdrowotna, Norwegia, szkoła, podstawa programowa, aktywność fizyczna, aktywność na świeżym powietrzu Streszczenie W pracy podjęto problem i analizę realizacji założeń edukacji zdrowotnej w norweskim systemie szkolnictwa. Porównano także wybrane założenia edukacji zdrowotnej w Norwegii do realizacji edukacji zdrowotnej w Polsce. Publikacja jest częścią przygotowywanej rozprawy naukowej, w której podjęto się empirycznej analizy wyników badań przeprowadzonych w szkołach polskich i norweskich. Keywords: health education, Norway, school, program, physical activity, outdoor activity Summary At work it was decided an issue analysis and implementation of health education in the Norwegian school system. Compares the selected assumptions of health education in Norway to implement health education in Poland. The publication is part of a planned dissertation, in which it was decided to the empirical analysis of the results of the tests carried out in schools Polish and Norwegian.